2020
DOI: 10.1177/0145561320963592
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Expanded Neck Flap for Face and Ear Reconstruction in Burn Patients: A Report on 2 Cases

Abstract: Reconstruction of auricular deformities and facial scars after burns is a challenging undertaking for surgeons. Excessive scar tissue, a poor blood supply and the paucity of available skin are all substantial difficulties that should be considered before the operation. Expanded neck flaps provide comparatively larger and thinner flaps for the simultaneous treatment of auricular deformities and facial scars in burn patients. In this article, the authors introduced the use of an expanded neck flap as coverage ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Extensive scarring was also visible on the forearm and supraclavicular region. Therefore, previous successful cases of framework prelamination in the above areas could not be emulated (1)(2)(3). We also immediately disregarded the modified Brent-Nagata's methods combined with skin grafting because a previous surgical exploration had found that the superficial temporal artery had been destroyed, making it difficult for the temporoparietal fascial flap to survive.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive scarring was also visible on the forearm and supraclavicular region. Therefore, previous successful cases of framework prelamination in the above areas could not be emulated (1)(2)(3). We also immediately disregarded the modified Brent-Nagata's methods combined with skin grafting because a previous surgical exploration had found that the superficial temporal artery had been destroyed, making it difficult for the temporoparietal fascial flap to survive.…”
Section: Case Presentationmentioning
confidence: 99%
“…After years of constant exploration, satisfactory burned ear reconstruction has been achieved by the combination of tissue expansion and distal composite framework prelamination followed by flap transfer to the defect location. The supraclavicular skin, neck skin, and medial forearm skin are the best alternative areas for the auricular framework prelamination for this process ( 1 - 3 ). When none of the above regions are available, using another area of hairless skin color matched to the periauricular area to cover the auricular framework may be possible, however, reports on this option are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Although the split-thickness-skin graft is a standard method of wound coverage in acute burn, the grafted skin shrinks over time 2) , resulting in variety of functional and aesthetic losses. Although the estimation of the original thermal damage to deeper structures is difficult for reconstructive surgeons, within this context, contracture release followed by thicker skin grafting or flap coverage is the most common procedure of burn reconstruction in order to improve the patient's quality of life 3,4) .…”
Section: Introductionmentioning
confidence: 99%